Solar-powered biometric security system: enhancing access control with sustainability - Mohammad Azhar, Nurin Hannani; Abu Bakar, Zahari; Kadiran, Kamaru Adzha; Khairul Anuar, Noor Hafizah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The Solar-Powered Biometric Security System redefines access control by integrating renewable energy with advanced biometric technology, offering a sustainable and secure solution for modern security challenges. This system utilizes two-factor authentication through motion detection and fingerprint recognition, significantly enhancing protection against unauthorized access. Powered by solar energy, it ensures uninterrupted operation even during power outages, making it ideal for remote locations or areas with unreliable electricity. The ESP8266 microcontroller is the system’s core, managing fingerprint data, controlling access points, and facilitating real-time monitoring via the Blynk IoT application. Users receive instant notifications and can remotely track access activity, reinforcing security awareness. Designed for residential, commercial, and industrial use, this eco-friendly system promotes energy efficiency while delivering robust, user-friendly security. Merging technology and sustainability represents a forward-thinking approach to safeguarding assets and enhancing convenience.